Psychometric evaluation of the body uneasiness test in the Arab Gulf region - Melisse, Bernou; el Khazen, Carine; de Beurs, Edwin (Frontiers in Psychology, 2025)
IntroductionThe Gulf Cooperation Council is experiencing socio-economic transformations, which coincides with exposure to Western beauty ideals and internalization of the Western thin-ideal, and consequently the development of body uneasiness. The present study psychometrically evaluates the Body Uneasiness Test, suitable for use in the Gulf Cooperation Council.MethodsAfter translation and back-translation, the Body Uneasiness Test was administered in a clinical sample (N = 169; all completed English version), and a community-based convenience sample (N = 544; n = 202, 37.1% in Arabic) between July 2024 and July 2025. Criterion validity was determined by two receiver-operating-characteristic curve analyses, one with sample type, and one with the Body Shape Questionnaire as a reference. A confirmatory factor analysis was used to determine the factor structure and T-scores and cutoff scores were established for females and males.ResultsInternal consistency was good (ω = 0.70–0.96), convergent validity was supported (r = 0.66–0.93), and the Body Uneasiness Test discriminated well between both samples (AUC = 0.70–0.94). Sensitivity to change was established in a subsample of 20 patients and was large (Cohen’s d = 1.97–2.20). Modified five- and eight-factor structures were confirmed.DiscussionThough some Gulf countries were underrepresented, the Body Uneasiness Test shows strong promise as a valid assessment tool for use in the Gulf Cooperation Council. However, item redundancy or overlap should be reviewed, and raw scores should first be normalized when utilizing the Body Uneasiness Test. Future research should examine test–retest reliability and further examine sensitivity to change.